2021
DOI: 10.3389/fpsyg.2021.528352
|View full text |Cite
|
Sign up to set email alerts
|

Acute Exercise-Induced Set Shifting Benefits in Healthy Adults and Its Moderators: A Systematic Review and Meta-Analysis

Abstract: Background: Positive effects of acute exercise on cognitive performances in general inspired research that investigated the effects of acute exercise on specific cognitive subdomains. Many existing studies examined beneficial effects of acute exercise on subsequent set shifting performance in healthy adults. Set shifting, a subdomain of executive function, is the ability to switch between different cognitive sets. The results of existing studies are inconsistent. Therefore, a meta-analysis was conducted that p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 89 publications
(91 reference statements)
1
10
0
Order By: Relevance
“…This appears to result in clinically relevant improvements, as the restored insulin-dependent FC was linked to better cognitive function after the exercise intervention. This is well in line with a recent metaanalysis that underlined aerobic exercise’s effects in improving cognitive flexibility ( 59 ).…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…This appears to result in clinically relevant improvements, as the restored insulin-dependent FC was linked to better cognitive function after the exercise intervention. This is well in line with a recent metaanalysis that underlined aerobic exercise’s effects in improving cognitive flexibility ( 59 ).…”
Section: Discussionsupporting
confidence: 89%
“…After the second fMRI measurement, cognitive function was evaluated by the trail making test (TMT). This measure of cognitive flexibility has been shown to improve in response to aerobic exercise ( 59 ).…”
Section: Methodsmentioning
confidence: 99%
“…A growing body of research has demonstrated a beneficial effect of acute exercise on cognition, particularly for tasks or task components with larger executive function (EF) demands [1][2][3][4][5]. Broadly defined, EF refers to a family of cognitive processes that enable the volitional control of thoughts, emotions, attention, and behaviors to complete task-oriented goals [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…They are also a key determinant of successful aging [9] and efficiency of daily living, an indispensable part of everyday life [10,11] Accordingly, sustaining and improving EF has become an important public health issue. Critically, previous studies have shown that EF is enhanced following a single bout (i.e., dose) of exercise (also called acute exercise) [1][2][3][4].…”
Section: Introductionmentioning
confidence: 99%
“…However, our knowledge regarding the influence of an adjusted exercise prescription on neurocognitive outcome parameters is meager. In this context, there are findings showing that exercise prescription of acute physical exercise [e.g., exercise intensity, mode of exercise protocol (continuous vs. interval training), or type of exercise (physical exercise with or without motor/cognitive activities)] influences neurocognitive parameters such as cognitive performance at the group level (Budde et al, 2008(Budde et al, , 2010Lambourne and Tomporowski, 2010;Chang et al, 2012;Netz, 2019;Oberste et al, 2019Oberste et al, , 2021Pontifex et al, 2019) or functional brain activity patterns (Mehren et al, 2019). Moreover, there is a good theoretical rationale that the exercise prescription influences the interindividual response variability of neurocognitive outcomes (Herold et al, 2019).…”
Section: Modifiable Exercise-related Factorsmentioning
confidence: 99%